Where in the World Are We Going? - Swidler, Leonard J. (Journal of ecumenical studies, 2017)
An editorial is presented that talks about a book written by the author titled "The Meaning of Life at the Edge of the Third Millennium" that sought to discuss the meaning of life. Topics discussed include a description by psychologist Abraham Maslow about the meaning of life, and the purpose of religion being to provide humans with an explanation of the meaning of life.